Concurrent Validity of the Biostage for Assessment of Lower Extremity Joint Angles. (September 2015) - Liu, Jian; Konz, Suzanne; Cheung, Felix H.; Szwilski, Tony B.; Chapman, Justin
The objective of the current study is to establish the concurrent validity of the Biostage, as a novel markerless motion analysis system, in measuring the lower extremity joint angles during a prescribed motion. Traditional markerless motion analysis system (e.g., Vicon Motus) was used as the baseline. A laboratory study involving 18 healthy young adults was conducted. Both the Biostage and the Motus were used to collect sagittal lower extremity joint angles while the subjects performed squats. The results indicated generally similar sagittal joint angle ensemble profiles between the systems. Significant differences in peak joint angles were found in hip joint, but not in ankle and knee joints. In conclusion, the study findings supported the concurrent validity of the Biostage, as a novel markerless motion analysis system, in measuring lower extremity joint kinematics.